GRAVITATIONAL-REDSHIFT PROPORTIONAL SIZE INCREASE IN RINDLER METRIC - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
The recently described gravitational-redshift proportional size change implicit in the Schwarzschild metric of general relativity and in the equivalence principle, is demonstrated geometrically in the Rindler metric. The result automatically carries over to general relativity (global constancy of c). Implications regarding terrestrial collision experiments, metrology, cosmology and unified physics are pointed out.